Of Men and Masculinity: The Portrayal of Masculinity in a Selection of Award-Winning Australian Young Adult Literature - Garrison, Kasey; Mary , Mary; Derouet, Elizabeth (Knygotyra, 2021)
This research investigates the portrayal of masculinity in Australian young adult novels published in 2019. The novels were taken from the 2020 Children’s Books Council of Australia (CBCA) Book of the Year for Older Readers Notables List. Established in 1946, these annual awards are considered the most prominent and prestigious in Australian children’s and young adult literature and are likely to be accessible and promoted to young readers in schools and libraries. The three texts studied were Four Dead Queens by Astrid Scholte, The Boy who Steals Houses by C.G. Drews, and This is How We Change the Ending by Vikki Wakefield. Using a Critical Content Analysis methodology (Beach et al., 2009), researchers completed a review of the literature and theories around masculinity and chose to analyse three exemplary texts using the attributes of the Hegemonic Masculinity Schema (HMS) and Sensitive New Man Schema (SNMS) as described by Romøren and Stephens (2002). Attributes from the HMS include traits and behaviours like being violent, physical or verbal bullying, and hostile to difference while attributes from the SNMS include being supportive, affectionate, and considerate and respectful of the space and feelings of others (especially females). In this method, researchers identify examples of the attributes within the main characters and minor characters from each of the three books, recording quotes and noting critical incidents depicting aspects of masculinity. Notable findings of the research include the acknowledgment and portrayal of a particular conception of hegemonic masculinity in the selected novels often informed or shaped by the presence of dominant father figures and the absence of the concept of “the mother.” The characters who aligned to the schema used within this research are often overshadowed by a dominant father figure who conformed to an extreme version of hegemonic masculinity and who shaped their child’s actions even if the fathers were absent from the novel. The research reveals commonly held conceptions of masculinity aligned to those used in the schema and demonstrated that young adult literature, like popular media, can be used as a vehicle for the dissemination of such concepts and reveal contemporary understandings of it. Outputs from this research include the development of a modified and more contemporary schema which could be applied to future research. Significantly, this interdisciplinary research bridges the library, education and literature fields to examine the different ways maleness and masculinity are depicted to young adult readers in prize-nominated Australian young adult novels.
Keywords: Hegemonic Masculinity; Critical Content Analysis; Young Adult Literature; You People’s Book Awards; Australian Book Award; Australian Young Adult Literature